Traitor's chase - Gibbs, Stuart, 1969- (Gibbs, Stuart. Last Musketeer, 2012)
"When the Musketeers pursue the dangerous Michel Dinicoeur to Spain, they're ambushed at every turn, causing them to suspect that there may be a traitor within their own ranks"--